2018
DOI: 10.1007/s12012-017-9441-z
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 Protects Against Paraquat-Induced Cardiac Contractile Dysfunction via RIP1-RIP3-MLKL-Dependent Necroptosis Pathway

Abstract: Paraquat is a highly toxic prooxidant that triggers oxidative stress and multi-organ failure including that of the heart. To date, effective treatment of paraquat toxicity is still not established. Necroptosis, a newly discovered form of programmed cell death, was recently shown to be strongly associated with cardiovascular disease. Receptor interaction proteins 1 (RIP1), receptor interaction proteins 3 (RIP3), and mixed lineage kinase domain like (MLKL) are key proteins in the necroptosis pathway. Necrostatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Necrostatin-1 (Nec-1) has been reported as an inhibitor of the receptor-interacting protein 1 (RIP1) kinase and a potent and specific inhibitor of necroptosis (25,26). Prior reports showed that Nec-1 could resolve inflammation by blocking RIP1 kinase activity in several experimental disease conditions, for example acute kidney injury, cardiac contractile dysfunction and brain injury after subarachnoid hemorrhage (27)(28)(29). Surprisingly, in our experiment, we unexpectedly found that Nec-1 inhibited NETs formation induced by phorbol 12-myristate 13-acetate (PMA).…”
Section: Introductionmentioning
confidence: 99%
“…Necrostatin-1 (Nec-1) has been reported as an inhibitor of the receptor-interacting protein 1 (RIP1) kinase and a potent and specific inhibitor of necroptosis (25,26). Prior reports showed that Nec-1 could resolve inflammation by blocking RIP1 kinase activity in several experimental disease conditions, for example acute kidney injury, cardiac contractile dysfunction and brain injury after subarachnoid hemorrhage (27)(28)(29). Surprisingly, in our experiment, we unexpectedly found that Nec-1 inhibited NETs formation induced by phorbol 12-myristate 13-acetate (PMA).…”
Section: Introductionmentioning
confidence: 99%
“…The animals (n=4 per group) were exposed to three doses of paraquat (low -10 mg/kg; moderate -50 mg/kg; and high -75 mg/kg). The doses were chosen from a range previously reported for cardiac research models in the literature, with reports showing that exposure at 40-80 mg/kg for up to 48 hours induced acute oxidative stress responses as well as reduced contractile function and calcium handling in the mouse heart [13,[15][16][17][18]. We first compared whether the applied paraquat doses elevated protein abundance of previously documented paraquat induced genes in the heart using mass spectrometry (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Paraquat (N,N-dimethyl-4,4bipyridinium dichloride) is a powerful pro-oxidant that generates mitochondrial reactive oxygen species in situ at the respiratory chain [9][10][11]. Acute paraquat exposure leads to significant multi-organ toxicity and mortality [12] and in laboratory experiments has been widely used as a model of oxidative stress in the heart [13,14]. We therefore compared the cardiac proteome between normal and paraquat-stressed mouse hearts using quantitative mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…21 Animal experiments demonstrated an important role for necroptosis in post-MI remodeling, 22 myocardial ischemia/reperfusion (I/R) injury, cardiotoxicity of doxorubicin treatment, 23, 24 and paraquat-induced cardiac contractile dysfunction. 25 Mechanistically, one elegant study has shown that cardiac necroptosis induced by I/R injury or doxorubicin treatment requires RIPK3 but not RIPK1 and MLKL; the upregulated RIPK3 phosphorylates and activates the calcium/calmodulin-dependent protein kinase II (CaMKII) and thereby opens mitochondrial permeability transition pore (MPT) to induce CM necroptosis. 23 However, more recent evidence suggests that the RIPK3-MLKL axis may still be important for myocardial necroptosis during I/R injury.…”
Section: Introductionmentioning
confidence: 99%